A Concept of Language Education for a Multilingual Symbiotic Society: Theory and Practice of Eric Hawkins' Language Education in the United Kingdom - KOYANAGI, Aki (THE JAPANESE JOURNAL OF EDUCATIONAL RESEARCH, 2022)
Due to the high mobility of populations, many countries, among them Japan, are facing challenges as multilingual and multicultural societies. Considering this situation, education preparing Japanese pupils for a multicultural and multilingual society is as important as education for pupils with foreign backgrounds. In this respect, multilingual education based on the concept of ‘language awareness” or ‘éveil aux langues” is gathering attention. While these multilingual education practices value the languages of pupils with foreign backgrounds and make Japanese pupils aware of linguistic diversity, they ignore the risk that Japanese pupils may retain their sense of superiority as the majority. This paper clarifies Eric Hawkins' concept of the subject 'language', the origin of the concept of 'language awareness', with the aim of relativising these educational practices and seeking education for a truly multilingual symbiotic society. This paper first reviewed the subject of ‘language's” educational objectives and the criticisms it faced. The subject ‘Language” was perfected in the 1970s, when changes in immigration and education policy brought together previously segregated pupils in the same classroom. Hawkins was concerned about two issues: low literacy and linguistic prejudice, which he summed up as the lack of pupils' 'autonomy'. To resolve this, he set the objective for the subject 'language' as ‘awareness of language”. For Hawkins, ‘awareness of language” was the conceptual view of language which the pupils would obtain when viewing language objectively. He believed that ‘awareness of language” could combat linguistic prejudice. This idea was criticised on two points: that meta-analysis of language might be nothing more than transcending static knowledge, and that it could overlook the inequalities created by the current social structure. To examine these criticisms, the details of the subject ‘language” are clarified in Chapter 2. In response to the first criticism at the curriculum level, ‘awareness” was thought to influence language use in other subjects. Therefore, the subject 'language' was considered to stimulate horizontal curriculum collaboration. In his topic book, Spoken and Written Language, Hawkins contrasted English and Chinese, aiming for the ‘awareness” that all language has ideographic function. Regarding the second criticism, Hawkins saw the curriculum as a sequence and set critical views of language in the Sixth Form, after the subject 'language'. In the topic book Using Language, he and Helen Astley posed analytical questions about language forms and language functions and presented value judgment questions about personal 'prejudice'. This also included references to prejudices arising from social structures, showing the potential of the subject ‘language”. This paper shows that the subject ‘language” tried to develop pupils' ‘awareness” as the basis for language use, linguistic tolerance and a critical view towards inequalities through the meta-analytical discussion of language. The subject ‘language” has two implications for Japanese education: 1. A curriculum with ‘language” as its core could serve as education for the multilingual symbiotic society; 2. The opportunity for all pupils to reflect on their language and to question their linguistic values can be worthwhile for true ‘linguistic tolerance”.